Platformization of Urban Life Towards a Technocapitalist Transformation of European Cities - Strüver, Anke; Bauriedl, Sybille (Urban Studies, 2022)
The increasing platformization of urban life needs critical perspectives to examine changing everyday practices and power shifts brought about by the expansion of digital platforms mediating care-services, housing, and mobility. This book addresses new modes of producing urban spaces and societies. It brings both platform researchers and activists from various fields related to critical urban studies and labour activism into dialogue. The contributors engage with the socio-spatial and normative implications of platform-mediated urban everyday life and urban futures, going beyond a rigid techno-dystopian stance in order to include an understanding of platforms as sites of social creativity and exchange.